Long-Term Prospects for the Development Energy Complex of Russia - Meynkhard, Artur (International Journal of Energy Economics and Policy, 2020)
The article discusses the long-term prospects for the development of the energy complex and its role in the Russian economy in the context of the restructuring of world energy markets and taking into account the draft Energy Strategy of the Russian Federation for the period up to 2035. Using the SCANER information complex, scenarios for the evolution of world energy markets and the corresponding scenarios for the development of the Russian economy and energy have been developed. The dynamics of domestic consumption of the main types of fuel and energy is analyzed taking into account energy conservation, as well as the effective size and direction of export of the main types of fuel. On this basis, the dynamics of the extraction and processing of the main types of fuel, the use of renewable energy resources and the production of electricity by different types of power plants were optimized, the sizes of capital investments necessary for this and the return on the dynamics of domestic prices for fuel and energy were determined. Corresponding to these scenarios, changes in the main macro-indicators of the contribution of the energy complex to the development of the Russian economy indicate the possibility of a relatively rapid reduction in its dependence on energy exports. Keywords: Energy export, energy efficiency, energy saving, energy security. JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.9064